Lider polityczny w totalitarnym i demokratycznym systemie politycznym. Pozorna opozycja? - Scheffs, Łukasz (Refleksje. Pismo naukowe studentów i doktorantów WNPiD UAM, 2018)
In traditional authority, the legitimacy of the authority comes from tradition, in charismatic authority from the personality and individual’s leadership qualities, and in rational-legal authority from powers that are bureaucraticly and legally attached to certain positions. Totalitarianism is a system of government. The leader has power without being restricted. Moreover, the leader is responsible for the monopolization of all human activities like artistic manifestations, political and communication systems. In democracy personalization exists. The personalization hypothesis states the individual has become more prominent at the expense of parties and collective identities. The question is: Are charismatic authority in totalitarianism and personalization in democracy identical?